Japan’s Challenges in Addressing Demographic Decline - Yonezawa, Akiyoshi (International Higher Education, 2024)
Facing an ongoing demographic decline, Japan’s higher education is now trying to develop new ecosystems for science, technology, innovation, and human resource development. The higher education system should engage with a wide range of stakeholders and be open in global, national and local dimensions with a long-term vision. Such a transformation in a dialogue between higher education and society is a major challenge, although the country does not have much time left before further decline.